Gaya Berpakaian Pria Pribumi di Sumatera Timur Awal Abad ke-20: Analisis Narasi Foto - Lukitaningsih Lukitaningsih; Parida Hasni; Haddad Wifaq Arraihan; Dimas Setiawan (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This study is a study of the clothing styles of indigenous men in East Sumatra which has the objectives of: 1) To find out the clotching styles of indigenous men in East Sumatra in the early 20th century; 2) To find out the relationship of clothing styles to the economic, social and cultural life of indigenous men in Sumatra. East early 20th century. This article uses historical research methods. The result of this study is that there is an influence of western clothing style with what was adopted by indigenous men in East Sumatra in the early 20th century. Among them are Toba Batak, Simalungun and Javanese coolies. This style of dress also affects a person's social position from the nobility, educated, workers, immigrants. Noble men appeared in hiou on tolugbalanga and soja as well as a number of makers of hats and accessories, noble men who were colonial servants usually appeared in corolondo clothes, intellectual or educated men used to wear corolondo clothes and robes, local men who were Christians usually wore shirts white with the bottom of the pants, and men who are Muslim usually appear with a bracket shirt. The influence of this dress appeared because of the colonial position in East Sumatra at that time so that the style of dress accompanied the daily life of the people in East Sumatra, from company owners, workers in company factories, regional aristocrats to ordinary people.